CD45 Opposes β-Amyloid Peptide-Induced Microglial Activation via Inhibition of p44/42 Mitogen-Activated Protein Kinase - Tan, Jun (J Neurosci, 2000)
Reactive microglia have been suggested to play a role in the Alzheimer's disease (AD) process, and previous studies have shown that expression of CD45, a membrane-bound protein-tyrosine phosphatase (PTP), is elevated in microglia in AD brain compared with controls. To investigate the possible role of CD45 in microglial responsiveness to β-amyloid (Aβ) peptides, we first co-treated primary cultured microglia with a tyrosine phosphatase inhibitor [potassium bisperoxo (1,10-phenanthroline) oxovanadate (phen), 5 μm] and freshly solubilized Aβ peptides (1000 nm). Data show synergistic induction of microglial activation as evidenced by tumor necrosis factor α (TNF-α) production and nitric oxide (NO) release, both of which we show to be dependent on activation of p44/42 mitogen-activated protein kinase (MAPK). Furthermore, co-treatment with phen and Aβ peptides results in microglia-induced neuronal cell injury. Stimulation of microglial CD45 by anti-CD45 antibody markedly inhibits these effects via inhibition of p44/42 MAPK, suggesting that CD45 is a negative regulator of microglial activation. Accordingly, primary cultured microglia from CD45-deficient mice demonstrate hyper-responsiveness to Aβ, as evidenced by TNF-α release, NO production, and neuronal injury after stimulation with Aβ peptides. As a validation of these findings in vivo, brains from a transgenic mouse model of AD [transgenic Swedish APP-overexpressing (Tg APP(sw)) mice] deficient for CD45 demonstrate markedly increased production of TNF-α compared with Tg APP(sw) mice. Taken together, these results suggest that therapeutic agents that stimulate the CD45 PTP signaling pathway may be effective in suppressing microglial activation associated with AD.